2014
DOI: 10.5688/ajpe7816
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Pharmacists’ Ability to Identify Drug-Related Problems in Patients Within a Patient-Centered Medical Home

Abstract: Objective. To quantify, describe, and categorize patient drug-related problems (DRPs) and recommendations identified by fourth-year (P4) student pharmacists during a live medication reconciliation activity within a patient-centered medical home (PCMH). Methods. Fourth-year student pharmacists conducted chart reviews, identified and documented DRPs, obtained live medication histories, and immediately provided findings and recommendations to the attending physicians. Documentation of DRPs and recommendations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…24 In contrast, pharmacy students in the study conducted by Armor and his colleagues reported that the incomplete medication list and the need for laboratory test were the two most common DRPs during their experiential clinical placement. 21 Notwithstanding, in a local study aimed to investigate the type of DRPs among diabetic subjects with underlying hypertension, reported that the two most common DRPs were insufficient health awareness and inappropriate drug choices. 25 The findings in our study were considered different from previous Swedish research that was carried out that revealed both inappropriate drug use and interactions were the most common DRPs identified by clinical pharmacists in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In contrast, pharmacy students in the study conducted by Armor and his colleagues reported that the incomplete medication list and the need for laboratory test were the two most common DRPs during their experiential clinical placement. 21 Notwithstanding, in a local study aimed to investigate the type of DRPs among diabetic subjects with underlying hypertension, reported that the two most common DRPs were insufficient health awareness and inappropriate drug choices. 25 The findings in our study were considered different from previous Swedish research that was carried out that revealed both inappropriate drug use and interactions were the most common DRPs identified by clinical pharmacists in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, the reported findings in our study are considered relatively higher in comparison with previous studies which reported 1.29, 1.53 and 1.93 DRPs per patient, respectively. 6,13,21 This shows that the frequency and type of identified DRPs may vary according to the setting. Accordingly, this variation may postulate some…”
Section: In Ward Managementmentioning
confidence: 95%
See 1 more Smart Citation
“…As a consequence, authors have been compelled to create their own definitions, generally based on their research objectives and method. In addition, we identified five studies that did not utilize the term medication discrepancy when describing the medication reconciliation process [24,30,[44][45][46], but instead used the terms 'DRPs or medication-related problems', 'inappropriate medication', 'prescribing error' and 'transcribing error'. It is noteworthy that the term 'medication error' has been used interchangeably with 'medication discrepancy' in several studies [40,[47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…2 The committee reviewed previous PAC reports pertaining to preceptor training and recognition, 3,4 the role of experiential education in practice, 5 and the collaboration of academic pharmacy and pharmacy practice. 6 In addition, a review of current AACP policy revealed several policies which pertain to the 2016-2017 PAC charges:…”
Section: Introductionmentioning
confidence: 99%